Revival of the penalty of short-term deprivation of liberty (Ius Novum, 2021)
The article discusses the issue of the revival of short-term deprivation of liberty in the Polish criminal law and justice system practice, the penalty, which was extensively applied in the interwar period. at the beginning of the paper the author presents widespread criticism of short-term penalties in the doctrine of the interwar period. at the same time she notices the approval of short-term penalties by the authors of the 1932 Criminal Code and an extensive scope of the imposition of the penalty of short-term deprivation of liberty. analysing the legal state and practice in the People’s republic of Poland, she presents the standpoint of the jurisprudence on the issue of short-term imprisonment, which challenged the role of this penalty as an adequate means of combating crime. the article also indicates scientists’ positive opinions about advantageous features of the penalty of short-term deprivation of liberty and its preventive function. Particular attention is drawn to the perception of a short-term penalty as an alternative to a long-term one and not an alternative to non-custodial penalties. the article also indicates the criticism of short-term imprisonment worldwide. Further comments characterise the idea of crime stratification and criminal liability polarisation that was laid down in the regulations of the 1969 Criminal Code, which raised the minimum length of a short-term penalty from one week to three months. it is established that in practice the idea of applying the penalty of short-term deprivation of liberty was implemented in the 1960s and after the introduction of the 1969 Criminal Code it was only strengthened. the analysis of the 1970s highlights the criticism of the penalty of deprivation of liberty in world jurisprudence and the collapse of the social rehabilitation model of that penalty execution. attention is drawn to the change in the standpoint of the doctrine on the issue of short-term imprisonment and acknowledgement that such penalties are less harmful than long-term penalties and may be useful for the purpose of the so-called shock therapy. Further deliberations focus on the presentation of the lawmaker’s stand and legal solutions of the 1997 Criminal Code, the establishment of the one-month minimum length of imprisonment and the adoption of regulations extensively promoting non-custodial penalties and measures. at the same time, the author presents the standpoint of the contemporary jurisprudence, which approves of the decrease in the minimum length of the penalty of deprivation of liberty and sees the need to return to the one-week imprisonment penalty as laid down in the 1932 Criminal Code. there is also an analysis of the practice of applying short-term imprisonment penalties in the period when the new Criminal Code came into force, which made it possible to establish that the actual return to short-term imprisonment penalties was accompanied by considerable decrease in one-year or two-year penalties in particular. it is also highlighted that the observed revival of the penalty of short-term deprivation of liberty and the abandonment of the opinion that such penalties are completely useless have demonstrated themselves in a new institution in the form of a mixed penalty combining the penalty of short-term deprivation of liberty and the penalty of limitation of liberty, which constitutes a form of legal response mainly to the so-called medium-weight crime and makes it possible to limit the scope of application of long-term imprisonment penalties. the article presents positive assessment of the revival of the penalty of short-term deprivation of liberty in the legislation and justice system practice.